MicroRNA-137 upregulation increases bladder cancer cell proliferation and invasion by targeting PAQR3. - Youcheng Xiu; Zan Liu; Shunyao Xia; Chengjun Jin; Huaifu Yin; Weiming Zhao; Qiong Wu (PLoS ONE, 2014)
There is increasing evidence suggesting that dysregulation of some microRNAs (miRNAs) may contribute to tumor progression and metastasis and have been proposed to be key regulators of diverse biological processes such as transcriptional regulation, cell growth and tumorigenesis. Previous studies have shown that miR-137 is dysregulated in some malignancies, but its role in bladder cancer is still unknown. In our study, we find that miR-137 is up-regulated in human bladder cancer tissues and cell lines. Moreover, the higher level of miR-137 was associated with pM or pTNM stage in clinical bladder cancer patients. Enforced expression of miR-137 in bladder cancer cells significantly enhanced their proliferation, migration and invasion. Bioinformatics analysis identified the tumor suppressor gene PAQR3 as a potential miR-137 target gene. Further studies indicated that miR-137 suppressed the expression of PAQR3 by binding to its 3'-untranslated region. Silencing of PAQR3 by small interfering RNAs phenocopied the effects of miR-137 overexpression, whereas restoration of PAQR3 in bladder cancer cells bladder cancer cells overexpressing miR-137, partially reversed the suppressive effects of miR-137. These findings indicate that miR-137 could be a potential oncogene in bladder cancer.